2009
DOI: 10.1080/13506120903090759
|View full text |Cite
|
Sign up to set email alerts
|

Increasing fatal AA amyloidosis in hunting falcons and how to identify the risk: a report from the United Arab Emirates

Abstract: Increasing fatal AA amyloidosis in hunting falcons and how to identify the risk: a report from the United Arab EmiratesHampel, M R Hampel, M R. Increasing fatal AA amyloidosis in hunting falcons and how to identify the risk: a report from the United Arab Emirates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…Edman degradation revealed a free N-terminus. The amino acid sequence of Herring gull protein AA from this study is shown in Fig 5 together with those from several avian and mammalian species [ 12 , 14 , 23 , 24 , 25 , 26 , 27 ]. As seen, the sequence was highly conserved but varied significantly at the N-terminus to the completely conserved F6 (numbering according to the human AA sequence).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Edman degradation revealed a free N-terminus. The amino acid sequence of Herring gull protein AA from this study is shown in Fig 5 together with those from several avian and mammalian species [ 12 , 14 , 23 , 24 , 25 , 26 , 27 ]. As seen, the sequence was highly conserved but varied significantly at the N-terminus to the completely conserved F6 (numbering according to the human AA sequence).…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, amorphous eosinophilic materials consistent with amyloid deposits were observed microscopically in one-third of affected and unaffected Herring gulls investigated during an outbreak of botulism [ 4 ]. Systemic amyloidosis has long been recognized in captive animals, including birds [ 8 , 9 , 10 , 11 , 12 ]. Marine and coastal birds in captivity, especially those of the orders Anseriformes , Gruiformes and Charadriiformes (to which genus Larus belongs) seem to be particularly prone to develop amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) as in Ruder et al 26 The occurrence of splenic amyloidosis is not surprising, as reactive systemic amyloidosis is not rare in birds and often occurs as a consequence of chronic inflammation and increased serum amyloid A protein. 7 …”
Section: Discussionmentioning
confidence: 99%
“…AA amyloidosis has been and still is a problem in the maintaining of several species of mammals and birds in captivity. It provides an economic loss in goose and duck farms , is associated with risk of extinction of certain species such as cheetah and causes loss of birds in falconry . The disease may also be important in the death of wild animals such as herring gulls in Sweden (Jansson et al ., unpublished data), European hares in Austria (A. Posautz, personal communication) and island foxes in California .…”
Section: Systemic Amyloidosismentioning
confidence: 99%